The relationship between household income and childhood respiratory health in the United Kingdom. - Violato, M; Petrou, S; Gray, R (2009)
Growing empirical evidence on the association between household income and adverse child health outcomes has generated mixed results with some North-American studies showing a significant inverse relationship and some British studies identifying a much weaker association. We use data from the rich UK Millennium Cohort Study (MCS) dataset and check the robustness of these recent findings by focusing on the impact of household income on adverse childhood respiratory outcomes (i.e. asthma and wheezing). We also identify pathways, such as mother's child-health-related behaviours, parental health and grandparental socioeconomic status, through which income might influence child health. Our econometric strategy is to use, both in a cross-sectional and in a panel data context, detailed information in the MCS dataset to directly account for as many potential confounding factors as possible that might bias the income-child health nexus. Overall our results show that household income has a weak direct effect on child health after we control for potential mechanisms that mediate the income-child health association. We argue that our evidence should inform government health and broader fiscal policies aimed at reducing health inequalities in childhood.